China's expectations for university students' employment outlook: A qualitative analysis based on employment policy documents - Zhang, Ziran; Hasan, Ahmad (Global Academic Excellence (GAE), 2024)
This study examines the influence of China's employment policies on university graduates' attitudes and career expectations. As a key part of the workforce, graduates' views on employment affect both individual career paths and social stability. Amid the Fourth Industrial Revolution, high-quality development demands, and challenges like the U.S.-China trade war, COVID-19, and demographic shifts, graduates in China face growing employment pressures. In response, the government has introduced policies to reduce these pressures and promote high-quality employment. Through a qualitative analysis of 13 policy documents from 2015 to 2023, this research explores what are China government and society's expectations to graduates’ employment. The analysis identifies four central themes: career direction, industry alignment, regional guidance, and employer type. The findings highlight a focus on value orientation, grassroots employment, and diverse career paths, urging graduates to combine personal goals with national development, seeking grassroots jobs, and exploring new economic opportunities.